Utopia 1516-2016 : More's eccentric essay and its activist aftermath - Sissa, Giulia, 1954-; Ruler, J. A. van, 1963- (Amsterdam University Press, 2017)
This year marks the five-hundredth anniversary of Thomas More's widely influential book Utopia, and this volume brings together a number of scholars to consider the book, its long afterlife, and specifically its effects on political activists over the centuries. In addition to thorough studies of Utopia itself, and appraisals of More's relationship with Erasmus, the book presents detailed studies of the effect of Utopia on early modern England and the Low Countries, as well as philosophical reflections on ideology and the utopian mind, and much more.
All articles in this book have been published in the journal Algemeen Nederlands Tijdschrift voor Wijsbegeerte, vol. 108 (2016) no. 3.
Keywords: More, Thomas, -- Saint, -- 1478-1535. -- Utopia.; Utopia (More, Thomas, Saint); Benelux countries.; England.; Angleterre.; Philosophy.; POLITICAL SCIENCE -- General.; PHILOSOPHY -- General.; Benelux countries; England; humanism, utopianism, history of political thought, ideology critique, thought experiments.; Electronic book.